An ecosystem enabling user-in-the-loop demand control in telecommunication andutility networks - Jaume Soler (An ecosystem enabling user-in-the-loop demand control in telecommunication andutility networks, 2018)
During the last decades the increment of the demand of scarce resources has increased in a dramatic way. Both water and energy have being exploiting irrationally, in addition with the climate change is leading us to an uncontrolled and unhealthy situation. In this research, a tool for Smart Home environment is presented whose aim is to be a first step to responsible each consumer in a household for its consumption. A whole system with sensors, gateway, actuators, servers etc. is going to be presented. As well as, the User-in-the-Loop paradigm will offer the possibility to take the blame the final user of its actions through a set of feedbacks.